Acoustically Driven Cell-Based Microrobots for Targeted Tumor Therapy - Hiep Xuan Cao; Van Du Nguyen; Daewon Jung; Eunpyo Choi; Chang-Sei Kim; Jong-Oh Park; Byungjeon Kang (MDPI AG, 2022)
Targeted drug delivery using microrobots manipulated by an external actuator has significant potential to be a practical approach for wireless delivery of therapeutic agents to the targeted tumor. This work aimed to develop a novel acoustic manipulation system and macrophage-based microrobots (Macbots) for a study in targeted tumor therapy. The Macbots containing superparamagnetic iron oxide nanoparticles (SPIONs) can serve as drug carriers. Under an acoustic field, a microrobot cluster of the Macbots is manipulated by following a predefined trajectory and can reach the target with a different contact angle. As a fundamental validation, we investigated an in vitro experiment for targeted tumor therapy. The microrobot cluster could be manipulated to any point in the 4 × 4 × 4 mm region of interest with a position error of less than 300 μm. Furthermore, the microrobot could rotate in the O-XY plane with an angle step of 45 degrees without limitation of total angle. Finally, we verified that the Macbots could penetrate a 3D tumor spheroid that mimics an in vivo solid tumor. The outcome of this study suggests that the Macbots manipulated by acoustic actuators have potential applications for targeted tumor therapy.